1999
DOI: 10.1016/s0042-6989(98)00250-8
|View full text |Cite
|
Sign up to set email alerts
|

A self-organizing neural system for learning to recognize textured scenes

Abstract: A self-organizing ARTEX model is developed to categorize and classify textured image regions. ARTEX specializes the FACADE model of how the visual cortex sees, and the ART model of how temporal and prefrontal cortices interact with the hippocampal system to learn visual recognition categories and their names. FACADE processing generates a vector of boundary and surface properties, notably texture and brightness properties, by utilizing multi-scale filtering, competition, and diffusive filling-in. Its context-s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
36
0

Year Published

2001
2001
2011
2011

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(38 citation statements)
references
References 67 publications
(45 reference statements)
1
36
0
Order By: Relevance
“…On the whole, GAM's performance did not improve with further training. As reported in Grossberg and Williamson (1998), these results arc Buperior to those obtained on a similar texture classification task by an alternative image classification architecture that used rule-based, multilayer perceptron, or knearest neighbor classifiers. GAM also outperformed this alternative architecture when they wme both evaluated on an identical task involving the classification of 10 natural textures.…”
Section: Classifying Natural Texturessupporting
confidence: 67%
See 1 more Smart Citation
“…On the whole, GAM's performance did not improve with further training. As reported in Grossberg and Williamson (1998), these results arc Buperior to those obtained on a similar texture classification task by an alternative image classification architecture that used rule-based, multilayer perceptron, or knearest neighbor classifiers. GAM also outperformed this alternative architecture when they wme both evaluated on an identical task involving the classification of 10 natural textures.…”
Section: Classifying Natural Texturessupporting
confidence: 67%
“…In order to evaluate the eJTeet of these changeB, 'I'AM was compared to GAM on natural texture classification benchmarks, on which GAM obtajned good results (Grossberg and Williamson, 1998). The dataset was produced by a biologically-motivated image processing system which extracted, from each 8x8 pixel region of an input image, 16 oriented contrast features (four orientations a.nd four spatial scales) a.s well as a. single brightness feature.…”
Section: Classifying Natural Texturesmentioning
confidence: 99%
“…"Back pocket models" based on the former were presented by (Fogel & Sagi, 1989;Malik & Perona, 1990;Landy & Bergen, 1991;Manjunath & Chellappa, 1993). The models of (Jain & Farrokhina, 1991;Grossberg & Williamson, 1999;Hofmann, Puzicha, & Buhmann, 1998) are using region based mechanisms to model texture segregation phenomena. However, psychophysical studies have revealed that in human texture perception both mechanisms are present: Some experiments (Nothdurft, 1985) have demonstrated that for certain stimuli edge based mechanisms are utilized, whereas other studies (Wolfson & Landy, 1998) showed that region based mechanisms are necessary to explain human texture segregation.…”
Section: Introductionmentioning
confidence: 99%
“…Although the texture segmentation performance of (Hofmann et al, 1998) is very good, this heuristic and the annealing framework itself are biologically not very plausible. A more promising approach is that from Grossberg and Williamson (Grossberg & Williamson, 1999). Their ARTEX model incorporates a self organizing network which gives remarkable classification results on multiple scale orientational contrast texture features.…”
Section: Introductionmentioning
confidence: 99%
“…Even without self-organization, such circuits have already yielded the most effective self-equilibrating boundary and surface representation algorithm that we have ever used for processing Synthetic Aperture Radar images [4]. In addition, simplified versions of these boundary mechanisms have been used to develop an architecture for self-organizing recognition categories in response to natural textures and textured Synthetic Aperture Radar images [ 43].…”
Section: Neocorticalmentioning
confidence: 99%